Study of the activity of Pt-Fe, Pd-Fe and Pt-Cu structured bi-metallic catalysts. Oxidation of VOC: toluene and ethyl acetate - Rosa Brussin, Marcos; Mendialdua, Juan; Casanova, Rodrigo; Hoffmann, Pedro; Torres, Alexander; Rueda, Fulgencio; Rodriguez, Alfonso; Rojas, Humberto (Ciencia)
In this work, Pt-Fe and Fe-Cu bi-metallic catalysts supported on monolithic structures composed of a clay mixture with alumina and zeolite FMI (3% Fe), were prepared separately. The incorporation of the metals was carried out using the simultaneous impregnation method in an approximate time of 30 min. then dried in air and calcinated for 4 h at 500°C. The catalysts obtained were used for VOC oxidation. For all catalysts studied, toluene completely oxidized to CO2 and H2O. In the case of ethyl acetate, at relatively low temperatures, partial oxidation products such as ethanol, ethers, acetic acid and acetaldehyde were formed. While oxidation was complete above 280°C. For Pt-Fe catalysts, the influence of the catalytic bed size in the activity was studied. The monolith with the greatest length (6 cm) was the most efficient, reaching toluene conversion > 90%, at elevated flow rate and lower temperatures than those of the remaining catalysts: Pd-Fe and Pt-Cu. The existence of extensive surface zones was determined by the SEM (mapping) technique, where the Pt-Fe and Pd-Fe bi-metallic pair separately, are associated. Iron improves dispersion of Pt microcrystals. XPS results obtained for the Pt-Fe catalyst, indicate an electronic promoter effect between Pt and Fe.